Kanker Batang: Penyakit Baru pada Kopi di Lampung - Suryo Wiyono; Andika Septiana Suryaningsih; Ali Wafa; Efi Toding Tondok; Bonjok Istiaji; Hermanu Triwidodo; Widodo Widodo (Jurnal Fitopatologi Indonesia, 2019)
Stem Canker: A New Disease of coffee in LampungStem cancer is a new disease that has attacked smallholder coffee plantations in Lampung since 2010. The cause of the disease was unknown. This study aims to describe the symptoms of the disease, the incidence of the disease in the affected plantation, and identify morphologically and molecularly the canker pathogens of the coffee stem canker diseases. All stages of Koch’s postulate were carried out in laboratories and greenhouses. The isolated pathogens were morphologically characterized by colony shape and color as well as the conidia shape and size. Molecular identification was carried out by using a general primer (ITS1 and ITS4) and followed by sequencing. The main symptoms of the disease are stem cancer and dieback, as well as more infecting older plants. Pathogen of the coffee stem canker disease that attacks coffee plants in Lampung has been identified as Fusarium solani which has 99% homology with F. solani KY245947.1.